(3LfhM GdCMOGK (B/ s - (3ESeGYjd, YRJ SjO s; (3EHQGgje, YRJ GdSjO s ((3GdchjJ (B: s (3hcGdI GdeWHhYGJ, s, 1984)
(3jTJed Ydi eLehYI ef CHMGK GdMdbI GdOQGSjI dQYGjI GdCMOGK GdLGfMjf HGdOhd GdYQHjI GdNdjLjI GdJj fXeJ NdGd TgQ eGjh (B1984 (3HGdefGeI(B. s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B. s
Keywords: (3LfGM GdCMOGKs -- (3Ohd GdNdjL GdYQHjI s; (3GdCWaGd s -- (3Yde faSs -- (3Ohd GdNdjL GdYQHjI s